Ideology and righteousness in Matt 5.20: a study in identity politics from the Sermon on the Mount - M‘bwangi, Fednand Manjewa (Department of Religious Studies, 2019)
The study focuses on the description of the function of the Sermon on the Mount in Matthew‘s Gospel. Not only does the Sermon on the Mount (SM) depict an ethical, eschatological and identity formation function, as it is popularly conceived by scholars, but it is also reflective of reconstruction, legitimation and the negotiation of the cultural identity of the community of Matthew in the city of Antioch, in Syria in the late first century CE. Through a Socio Rhetorical Interpretation (SRI), the analysis of the SM has been found to be reflective of the negotiating of identity politics of the community of Matthew in the aftermath of the destruction of the second Jerusalem temple, following the 66-73 Jewish revolt against Rome. Thus, the implied author of the SM employs the rhetorical function of the SM to consolidate a Christian community in the aftermath of the destruction of the second Jerusalem temple by contesting the Roman empire, borrowing from Israel‘s religious heritage and, accommodating the Jesus Movement. Consequently, pursuant to identity politics guided by the requirements of righteousness in Matt 5.20, the SM provides a basis for the reconstruction of a superordinate cultural identity for the community of Matthew that embraced both Judeans and the Gentiles. The reconstruction of a superordinate identity for the Matthean community enabled the implied author of the SM to effectively address intra-ethnic conflict that had characterized the Jesus Movement about 35 years before the emergence of the community of Matthew. Thus, the study has established that a creation of a superordinate identity provides the impetus for addressing intraethnic conflict situations because it embraces a dual identity, that is, a common identity to which other aspects of identity are subordinated.